Polymer nanocomposites: Why their mechanical performance does not justify the expectation and a possible solution to the problem? - S. Fakirov (eXPRESS Polymer Letters)
The expected order-of-magnitude enhancement in modulus (at loadings less than 1%) of polymer nanocomposites has proven elusive – the observed improvements are 10–35% only. The failure of the concept has been attributed to poor dispersion, poor interfacial load transfer, process-related deficiencies, and others. Due to the inherent property of the nano-size materials, their extremely high specific surface, they tend to agglomerate, and their further dispersion in the matrix component is practically impossible. For this reason, the composites prepared via blending a polymer with a nano-size material are microcomposites instead of nanocomposites, as demonstrated by light scattering studies. So long as reliable tools and/or techniques for proper dispersion of nanomaterials are missing, we must use methods free of the dispersion step in the manufacturing process. The relatively new ‘concept of converting instead of adding’ offers two such techniques – instead to take the matrix and the reinforcement in their final form and blend them, one takes one component only and during the processing creates the missing second component. Both approaches result in true nanocomposites with superior mechanical performance – the improvements of the tensile strength for nanofibrillar polymer-polymer and single polymer composites are up to 200 and 440%, respectively, (or even up to 650% if trans-reaction catalyst is used).